KEPUASAN MAHASISWA KEPERAWATAN TAHUN KEDUA TERHADAP PELAYANAN LABORATORIUM STIKES DIRGAHAYU SAMARINDA - Norsanah Norsanah (Poltekkes Kemenkes Kalimantan Timur, 2019)
Customer satisfaction by it has been determined by how cutomer expectations are met. Customer satisfaction is directly connected to customer needs. The extent to which these needs are, determines pleasure in cases of disappointment or disappointment because of differences. This study aims todetermine “student satisfaction with laboratory services among second years nursing students stikes dirgahayu samarinda”. The research design was descriptive reesearch, while the sample in this study were second-year nursing students who used a facility laboratory more than 10 times, amounting to 61 people. The results showed that 55,7% of respondents were satisfied and 44,3% of respondent were very satisfied with the dimensions of tangibles, 59,0% of respondents were satisfied and very satisfied 37,7% of the Responsiveness dimension, 65,6% of respondents were satisfied and 34,4% very satisfied with the dimension of Reability, 75,4% of respondents were satisfied and 24,6% were very satisfied with the dimension of Empaty and 72,1% of respondents werw satisfied and 16,4% very satisfied with the dimension of Assurance. The results showed that respondent’s satisfaction was the in the satisfied category with 5 (five) dimension which were indicators of satisfaction. Researcher’s suggestion for the results of the research is that laboratory officers can improve services in the laboratory with additional facilities not only from quantity but quality by paying attention to indicators of satisfaction which include the dimensions of Responsiveness and Assurance.